Community ecology of free-living marine nematodes in Sarawak coastal waters - Chen, Cheng Ann (Universiti Malaysia Sarawak (UNIMAS), 2010)
(This is the pioneer study focused on the community study of marine nematode (until the species, level) in Sarawak. The surveys on the marine nematode were carried out at 20 sites along the Sarawak coastal waters. A total of 87 species of marine nematode had been recorded along the Sarawak coastal waters. Miri Beach had the highest abundance and species number of marine nematodes followed by Sematan River. Results showed that the abundance of the marine nematode in the coastal study was significantly different (p-value < 0.05) and correlated to the four parameters: pH, DO, sand and silt (correlation = 0.311). In the horizontal study of the nematode in Teluk Awar (Kuching), particle size fractions showed no significant difference between sites (p-value > 0.05) but significantly different between stations (p-value < 0.05; R-statistic = 0.349))The result of the present study showed that the marine nematode assemblages in Teluk Awar were mostly dominated by the functional feeding group (FFG) of IB and 2B type except for station B2, A9 and B9. Vertical study of nematode in Teluk Awar showed that at the depth of 0-5 cm, the recorded species were Daptonema hirstum (70.48%) and Daptonema tenuispiculum (20.26%) with the average similarity of 10.81. The nematode species was not found below 15 cm sediment depth. Different pattern of nematode abundance is recorded in the sandy and muddy site for the seasonal study. The seasonal study showed that the marine nematode community structure not only affected by the particle size fractions (sandy /muddy) but also the seasonal rainfall.